Quadriceps Strengthening Education for Elderly with Knee Osteoarthritis in Cisadea Public Health Center Malang: Edukasi Penguatan Quadriceps pada Lansia Penderita Osteoartritis Lutut di Puskesmas Cisadea Malang - Faisal Yuliansyah; Anita Faradilla Rahim; Doni Oktavianto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Osteoarthritis (OA) is a disorder that occurs in the joints characterized by degradation of the joint cartilage. Osteoarthritis attacks individuals aged 70 years and over. Factors that trigger osteoarthritis include obesity or excess body weight, age, gender, history of trauma and activities with excessive load and intensity. Knee OA is the result of progressive loss of articular cartilage. Delivering education about quadriceps strengthening aimed at elderly people with knee osteoarthritis aims to reduce complaints of pain they feel. The introduction of quadriceps strengthening exercises uses the drill and practice method, namely by continuously practicing movements repeatedly to reduce the level of knee pain. When providing education regarding quadriceps strengthening exercises to the elderly, they seemed happy and enthusiastic in implementing every direction and movement. It is hoped that this activity can be carried out regularly by the elderly to reduce pain complaints in the elderly.